The role of cellulases and glucohydrolases in the solubilisation of primary sewage sludge - Ngesi, Nosisa (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2002)
Biological sulph ate reduction has been identi fied as a potentially valuable process for removing sulphate and heavy metals from indllstrial effluents. The role of sulphate reducing bacteria (SRB) in this process has attracted the attention of biotechnologists and recently of enzymologists due to its fundamental properties and possible role in AMD bioremediation. These obligatory anaerobic sulphate-reducing bacteria are commonly known to dissimilate sulphate for energy. Under anaerobic conditions SRB oxidize simple organic compounds such as lactic acid with the sulphate and thereby generate hydrogen sulphide (a stTong reducing agent) and bicarbonate ions. The hydrogen sulphide in turn reacts with contaminant metals contained in AMD and precipitates them out of solution as metal sulphides. Bicarbonate ions neutralize AMD by reaction with protons to form carbon dioxide and water. Organic matter in the municipal sewage sludge has been identified as a potential source of electron donors for su lphate reduction. However, this organic matter is in the polymeric form that cannot be util ised by SRB. The latter depend on the activities of other hydrolytic bacteria for the degradation of complex polymers. Hence the availability of these monomeric substrates is a major factor, which may constrain further process development and is considered a rate-limiting step. Thi s study is therefore undertaken to investigate the bacterial glucohydrolase enzymes involved in the digestion of the polysaccharides present in the sewage sludge with specific interest in cellulases and/or p-glucosidase enzymes. The goals of the research are to: isolate, identify, purify and quantify these enzymes; study their distribution with respect to time, pH, and temperature; maximize and quantify the hydrol ys is products; study whether sulphide and sulphate have an enhancing or an inhibitory effect on the activity of enzymes; optimize the enzyme activity against substrate and/or product inhibition and soluble heavy metal salts.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Sewage sludge; Sewage sludge digestion; Cellulase; Glucosidase inhibitors; Hydrolases; Sulfates